Chemotherapy in synergy with innate immune agonists enhances T cell priming for checkpoint inhibitor treatment in pancreatic cancer - Nan Niu; Keyu Li; Junke Wang; Vanessa Funes; Birginia Espinoza; Pan Li; Jianxin Wang; Melissa Lyman; Mengni He; Brian Herbst; Michael Wichroski; Ruslan Novosiadly; et al. (Biomarker Research)
Abstract Background The combination of conventional chemotherapy and immune checkpoint inhibitors (ICIs) has been unsuccessful for pancreatic ductal adenocarcinoma (PDAC). Administration of maximum tolerated dose of chemotherapy drugs may have immunosuppressive effects. Methods We thus tested, by using the preclinical model of PDACs including the genetically engineered mouse KPC spontaneous pancreatic tumor model and the pancreatic KPC tumor orthotopic implant model, the combinations of synthetic innate immune agonists including STING and NLRP3 agonist, respectively, and ICIs with or without chemotherapy. Results We found that innate agonists potentiate the role of chemotherapy in inducing effector T cells and subsequently to prime the tumor microenvironment (TME) better for ICI treatments. Triple combination of chemotherapy, innate agonists, and ICIs is superior to single modalities or double modalities in antitumor efficacies. Adding chemotherapy to innate agonists enhances the infiltration of overall CD8+ T cells and the memory cytotoxic subtype. NLRP3 agonist has a less effect than STING agonist on driving the T cell exhaustion. Adding chemotherapy to innate agonists enhances the infiltration of dendritic cells (DCs) in the tumors and CD86+ mature DCs in tumor draining lymph nodes. RNA sequencing analysis of the pancreatic tumors demonstrates the role of the combination of STING/NLRP3 agonist and chemotherapy, but not either treatment modality alone, in upregulating the T cell activation signaling. The NLRP3 agonist-mediated T cell activation is likely through regulating the nitrogen metabolism pathways. Conclusion This study supports the clinical testing of both STING and NLRP3 agonists, respectively, in combination with chemotherapy to sensitize PDAC patients for ICI treatments.